2010
DOI: 10.3109/13693786.2010.540044
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to buccal epithelial cells, enzymatic and hemolytic activities ofCandida isolatesfrom HIV-infected individuals

Abstract: Candida spp., along with other microorganisms are usually found in the normal flora of the human oral mucosa. However in HIV-infected individuals these yeasts can become opportunistic pathogens and lead to mucosal infections. The transformation from a harmless commensal to a virulent pathogen under conditions of dysfunctional host defense system is attributable to an extensive repertoire of selectively expressed virulence determinants. The present study was undertaken to analyze the production of four importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
18
0
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 19 publications
10
18
0
6
Order By: Relevance
“…Hemolytic activity of Candida species did reports in many studies, previously [20,21,23,33]. In the study by Mane et al [20], 100% of the C. albicans isolates had beta hemolytic activity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Hemolytic activity of Candida species did reports in many studies, previously [20,21,23,33]. In the study by Mane et al [20], 100% of the C. albicans isolates had beta hemolytic activity.…”
Section: Discussionmentioning
confidence: 88%
“…The complex is visible as insoluble crystals around the colony. The hemolytic factor of Candida species was described by many investigators [19,20,21,33,36]. Since C. albicans can utilize iron that is contained in hemoglobin and can rosset complement, opsonized surface red blood cell (SRBC), a hemolysis assay was developed to determine hemolytic factor to lyse erythrocytes [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we evaluated a number of C. glabrata (n = 13) similar to the number of C. albicans (n = 20) strains, while the number of samples of C. glabrata was much lower compared to C. albicans in previously cited studies. 17,22 These data show the need for more studies with C. glabrata, which recently was shown to have the ability to produce α or β hemolysis. This species has emerged as a potential pathogen in the oral cavity of immunocompromised patients and little is known about its role in infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, Mane et al 22 analyzed the hemolytic production of 65 Candida isolates from HIV-infected individuals and verified that C. albicans (n = 39) produced more hemolysin compared to all other species, including C. glabrata (n = 8). Ramesh et al 17 also evaluated the hemolytic capacity of 50 Candida strains from HIV patients, and verified that C. albicans (n = 45) produced a significantly higher amount of hemolysin than C. glabrata (n = 5).…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase and proteinase production was found in 100% of C. albicans isolates during this study. However, MANE et al 21 verified production of phospholipase and proteinase in only 59% and 89.7%, Among the isolates of non-albicans species identified in this study, 39% showed phospholipase activity and 21% exhibited proteinase activity. Previous studies also reported that proteinases and phospholipases are produced at high rates in C. albicans, whilst non-albicans Candida species usually present low rates of these enzymes 5,8 .…”
mentioning
confidence: 98%